Pengaruh Laba Kotor, Laba Operasi Dan Laba Bersih Terhadap Arus Kas Di Masa Mendatang Pada Perusahaan Subsektor Kosmetik Yang Terdaftar Di Bursa Efek Indonesia - Nunung Hasanah; Supiningtyas Purwaningrum (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to analyze the effect of gross profit, operating profit, and net profit on future cash flows in cosmetic subsector companies listed on the Indonesia Stock Exchange during the period 2014–2023. This research uses a quantitative approach with multiple linear regression analysis. The sampling technique used is purposive sampling, resulting in three cosmetic subsector companies as research samples. The data used are secondary data obtained from the annual financial statements published by the Indonesia Stock Exchange and the official websites of the respective companies. The results of the study indicate that partially gross profit, operating profit, and net profit have a significant effect on future cash flows. Simultaneously, gross profit, operating profit, and net profit significantly affect future cash flows in cosmetic subsector companies listed on the Indonesia Stock Exchange. These findings indicate that profit information can be used as an important indicator in predicting future cash flows.